Para badminton World Championships perspectives from 2013 to 2024 - Petrinovic, L.; Juriša, L.; Trošt Bobic, T. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Para Badminton is a sport gaining increasing popularity worldwide, which has led to its inclusion as a full medal sport at the Paralympic Games 2021 in Tokyo. Each athlete is classified into one of the six Sport Classes before competing at the international level, ensuring fair competition by grouping athletes based on how their physical impairment affects their performance as badminton players. For this paper, the available data about the played matches from Para Badminton World Championships in 2024 and 2013 were compared in order to gain a clearer understanding of the ten-year development of Para Badminton as a sport. In wheelchair classes, there was a significant difference between matches` duration of Men`s Singles in 2024 and 2013, with the first lasting longer, as well as Men`s Singles in 2024 and Women`s Singles in 2024. In the comparison of standing classes, there was no statistical significance, but the trend of longer matches` durations in 2024 was evident. The difference shown could witness Para Badminton development over the years by describing a better quality of players` performance, leading to a longer matches` duration.